"Are you accepting new patients?" A pilot field experiment on telephone‐based gatekeeping and Black patients' access to pediatric care. (3rd December 2018) - Leech, Tamara G.J.; Irby‐Shasanmi, Amy; Mitchell, Anne L.
Abstract : Study Objectives: To determine whether name and accent cues that the caller is Black shape physician offices' responses to telephone‐based requests for well‐child visits. Method and Data: In this pilot study, we employed a quasi‐experimental audit design and examined a stratified national sample of pediatric and family practice offices. Our final data include information from 205 audits (410 completed phone calls). Qualitative data were blind‐coded into binary variables. Our case‐control comparisons using McNemar's tests focused on acceptance of patients, withholding information, shaping conversations, and misattributions. Findings: Compared to the control group, "Black" auditors were less likely to be told an office was accepting new patients and were more likely to experience both withholding behaviors and misattributions about public insurance. The strength of associations varied according to whether the cue was based on name or accent. Additionally, the likelihood and ways office personnel communicated that they were not accepting patients varied by region. Conclusions: Linguistic profiling over the telephone is an aspect of structural racism that should be further studied and perhaps integrated into efforts to promote equitable access to care. Future research should look reactions to both name and accent, taking practice characteristics and regional differences into consideration.